1982
DOI: 10.1108/eb024106
|View full text |Cite
|
Sign up to set email alerts
|

Measures that discriminate among online searchers with different training and experience

Abstract: The major research objectives were to identify the differences among the searchers of users of online bibliographic systems who have different backgrounds of training and experience, and the differences among the searches of persons with and without experience of the Eric database. A quasi‐experimental research design used forty‐two searchers separated into five experience levels who conducted two pre‐selected searches using the Dialog system and the Eric database. The results were measured with variables whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 5 publications
4
35
2
Order By: Relevance
“…It is now more difficult to define how long people have been searching online and they find it hard to remember how they learnt to do so. Thus, definitions like Harter's (1984) and Howard's (1982) which relied on attendance at specific courses or the number of searches performed over time, are no longer meaningful. It is also more difficult to decide what is meant by a single search.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now more difficult to define how long people have been searching online and they find it hard to remember how they learnt to do so. Thus, definitions like Harter's (1984) and Howard's (1982) which relied on attendance at specific courses or the number of searches performed over time, are no longer meaningful. It is also more difficult to decide what is meant by a single search.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the 1980s defined novices as those who had not undertaken independent online searching, or had undertaken a beginners' course in information seeking, (Howard, 1982;Harter, 1984) and defined expertise in terms of the number of searches carried out over a certain period, for example a month, (Howard, 1982) or for a certain time prior to the study (Harter, 1984). Later studies have followed a student group from relative inexperience to the attainment of far greater expertise (Whitmire, 2002;Vakkari, 2001;Wilson et al 2002;Kuhlthau, 2004;Spink et al, 2002a and b), and thus the experts and novices are, in effect, the same group of participants at different stages of development.…”
Section: Experts and Novicesmentioning
confidence: 99%
“…One possible solution is to identify the user characteristics and their relationship with system features that may contribute to better search performance. However, previous research on the impact of user characteristics in the use of information retrieval systems has suggested that (a) domain knowledge or specific topic knowledge is not correlated with search outcome (Allen, 1991;Pao, Grefsheim, Barclay, Woolliscroft, McQuillan, & Shipman, 1993) and (b) search experience with databases cannot predict search outcome (Fenichel, 1981;Howard, 1982;Sutcliffe, Ennis, & Watkinson, 2000). That raises the question in what specific conditions these system features like human-developed index terms and automatic indexing techniques will be useful for different kinds of users.…”
Section: Problem Statementmentioning
confidence: 79%
“…Previous research on impact of searcher characteristics, particularly domain knowledge and search experience, on search effectiveness has been inconclusive (Fenichel, 1981;Howard, 1982;Hsieh-Yee, 1993;McKibbon, Haynes, Walker Dilks, Ramsden, Ryan, Baker, L., et al, 1990;Pao et al, 1993). It is still unclear for which kinds of searchers the MeSH terms will be most useful in the context of searching complex biomedical topics.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation